The Gardner syndrome: a cell culture study on kindred 109. - Danes, B S (1978)
In vitro studies on skin cultures established from 49 members from Kindred 109, in whom the Gardner syndrome was first delineated, showed that increased in vitro tetraploidy occurred only in those cultures derived from branches with the full expression of the Gardner gene (colorectal polyps with multiple extracolorectal benign tumours) and not in those derived from branches showing only extracolorectal lesions. Increased in vitro tetraploidy appeared to identify only those family members at risk who had, or would ultimately be expected to show, full expression of the Gardner gene including colorectal polyps which become malignant.